1981
DOI: 10.1029/wr017i004p01191
|View full text |Cite
|
Sign up to set email alerts
|

Scale‐dependent dispersion in a stratified granular aquifer

Abstract: The magnitude of longitudinal dispersivity in a sandy stratified aquifer was investigated using laboratory column and field tracer tests. The field investigations included two‐single‐well injection‐withdrawal tracer tests using 131I and a two‐well recirculating withdrawal‐injection tracer test using 51Cr‐EDTA. The tracer movement within the aquifer was monitored in great detail with multilevel point‐sampling instrumentation. A constant value for dispersivity of 0.7 cm was found to be representative (and indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
241
4
3

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 442 publications
(263 citation statements)
references
References 36 publications
9
241
4
3
Order By: Relevance
“…This phenomenon, called the dispersion scale effect, has been observed repeatedly in groundwater experiments [Pickens and Grisak, 1981;Sudick32 et al, 1983;Freyberg, 1986].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…This phenomenon, called the dispersion scale effect, has been observed repeatedly in groundwater experiments [Pickens and Grisak, 1981;Sudick32 et al, 1983;Freyberg, 1986].…”
Section: Introductionmentioning
confidence: 96%
“…The dispersion behavior observed in these experiments is usually attributed to heterogeneity in the saturated hydraulic conductivity of the aquifer [Pickens and Grisak, 1981 [Freyberg, 1986].…”
Section: Introductionmentioning
confidence: 99%
“…It has been clearly demonstrated in the literature, both experimentally and theoretically, that dispersivity is positively correlated with the scale of observation [Pickens and Grisak, 1981;Gelhar and Axness, 1983;Neuman, 1990]. One school of thought hypothesizes that a L initially increases linearly with scale of observation and then gradually approaches a constant asymptotic value at an upper bound, which corresponds to the representative elementary volume (smallest volume of a porous medium over which measurements made are representative of the whole) [Gelhar et al, 1992].…”
Section: Hydrodynamic Dispersion and Dispersivitymentioning
confidence: 99%
“…Numerous laboratory and field-scale studies have focused on estimation of either the longitudinal dispersion coefficient [Harleman and Rumer, 1963;Pickens and Grisak, 1981;Koch and Brady, 1985;Han et al, 1985;Chrysikopoulos et al, 1990;Delgado, 2006] or the transverse dispersion coefficient [Delgado and Guedes de Carvalho, 2000;Cirpka et al, 2006;Acharya et al, 2007;Olsson and Grathwohl, 2007]. Transverse dispersion is increasingly recognized as a controlling mass transfer mechanism for contaminant plume migration and NAPL dissolution in aquifers [Chrysikopoulos et al, 1994;Chrysikopoulos and Kim, 2000;Chrysikopoulos et al, 2003;Rahman et al, 2005;Cirpka et al, 2006;Acharya et al, 2007;Rolle et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, α x = 0.1 * (plume length) or α x = 0.1 * ((plume length) / 2). This approach provides a good general estimate and is consistent with the derivation of the Domenico solution; however, various investigators have shown that calculating a varying α x throughout the plume as a function of x provides a superior match to field data (Pickens and Grisak, 1981;EPA, 2000). Typically α x = 0.1 * (x).…”
Section: Moving Toward a Mass Balance Approachmentioning
confidence: 76%